Contrarian and momentum strategies: Evidence in Chile - González A., Marcelo (Estudios de Administración, 2006)
This study analyses the possibility of getting economical gains (riska djusted) through two strategies, based only, in the historical trend of the prices. The Contrarian strategy, De Bondt y Thaler (1985), is based in the reversion of the trend of the prices, and the Momentum strategy, Jegadeesh y Titman (1993), which is based in the continuation of the trend in the prices. The contrarian strategy classifies the stocks based in their performance during a previous 5 years period, and recommends to buy the past losers, to sell the past winners and to keep them during a 3 to 5 years period. In a similar way, the momentum strategy, recommends to buy the past winners, to sell the past losers and to keep them during a 3 to 12 months period. Testing the existence of theses anomalies in the Chilean market it is found, significant (theoretical) returns for a formationtest period of 24 months, in the case of the contrarian strategy and, significant (theoretical) returns for a formation-test period of 6 months, in the case of the momentum strategy.